Effect of a Laboratory Result Pager on Provider Behavior in a Neonatal Intensive Care Unit - Samal, L.; Stavroudis, TA.; Miller, RE.; Lehmann, HP.; Lehmann, CU. (Applied Clinical Informatics, 2011)
Background: A computerized laboratory result paging system (LRPS) that alerts providers about abnormal results (“push”) may improve upon active laboratory result review (“pull”). However, implementing such a system in the intensive care setting may be hindered by low signal-to-noise ratio, which may lead to alert fatigue.Objective: To evaluate the impact of an LRPS in a Neonatal Intensive Care Unit.Methods: Utilizing paper chart review, we tallied provider orders following an abnormal laboratory result before and after implementation of an LRPS. Orders were compared with a predefined set of appropriate orders for such an abnormal result. The likelihood of a provider response in the post-implementation period as compared to the pre-implementation period was analyzed using logistic regression. The provider responses were analyzed using logistic regression to control for potential confounders.Results: The likelihood of a provider response to an abnormal laboratory result did not change significantly after implementation of an LRPS. (Odds Ratio 0.90, 95% CI 0.63–1.30, p-value 0.58) However, when providers did respond to an alert, the type of response was different. The proportion of repeat laboratory tests increased. (26/378 vs. 7/278, p-value = 0.02)Conclusion: Although the laboratory result pager altered healthcare provider behavior in the Neonatal Intensive Care Unit, it did not increase the overall likelihood of provider response.
Keywords: Medical informatics applications; reminder systems; clinical laboratory information systems; hospital communication systems; time factors